Dye‐Sensitized Solar Cells with Vertically Aligned TiO2 Nanowire Arrays Grown on Carbon Fibers. Issue 2 (20th December 2013) - Cai, Xin; Wu, Hongwei; Hou, Shaocong; Peng, Ming; Yu, Xiao; Zou, Dechun
Abstract One‐dimensional semiconductor TiO2 nanowires (TNWs) have received widespread attention from solar cell and related optoelectronics scientists. The controllable synthesis of ordered TNW arrays on arbitrary substrates would benefit both fundamental research and practical applications. Herein, vertically aligned TNW arrays in situ grown on carbon fiber (CF) substrates through a facile, controllable, and seed‐assisted thermal process is presented. Also, hierarchical TiO2‐nanoparticle/TNW arrays were prepared that favor both the dye loading and depressed charge recombination of the CF/TNW photoanode. An impressive conversion efficiency of 2.48 % (under air mass 1.5 global illumination) and an apparent efficiency of 4.18 % (with a diffuse board) due to the 3D light harvesting of the wire solar cell were achieved. Moreover, efficient and inexpensive wire solar cells made from all‐CF electrodes and completely flexible CF‐based wire solar cells were demonstrated, taking into account actual application requirements. This work may provide an intriguing avenue for the pursuit of lightweight, cost‐effective, and high‐performance flexible/wearable solar cells.